Energy Levels and the Landé g-Factors for Singly Ionized Lanthanum. (5th June 2013) - Karaçoban, Betül; Özdemir, Leyla
Abstract : We have calculated the energies and the Landég -factors for 5d 2, 5d6s, 6s 2, 4f6p, 5d7s, 5d6d, 4f 2, 6p 2, 6s6d, 6s7s, 4f6s, 4f5d, 5d6p, 6s6p, 4f7s, 4f6d, 5d7p, and 6s7p excited levels of singly ionized lanthanum (La II). These calculations have been carried out by using the multiconfiguration Hartree-Fock method within the framework of the Breit-Pauli Hamiltonian (MCHF+BP) and the relativistic Hartree-Fock (HFR) method. The obtained results have been compared with other works available in the literature. A discussion of these calculations for La II in this study has also been in view of the MCHF+BP and HFR methods.